A study on the determination of two related aminothiols in the brain of diabetes rats by HPLC-ECD. Issue 17 (7th November 2020) - Li, Jian-Sha; Huang, Dan; Qiu, Hong-Mei; Jiang, Qing-Song; Liu, Yong-Hong; Du, Ting-Ting; Jiang, Xin-Hui
Abstract: A high-performance liquid chromatography-electrochemical detection method was developed to determine the concentration of homocysteine and cysteine in the diabetes mellitus Sprague-Dawley male rats' cortex and hippocampus. The cortex and hippocampus of control and diabetes model rats were collected. After pretreatment, the analysis of total homocysteine and cysteine were performed on a C8 column. Under the optimized analytical conditions, the linear correlation coefficients were higher than 0.999 in the concentration range from 0.148 to 22.193 μmol.L −1 with the limit of quantitation of 0.083 μmol.L −1 . The extraction recoveries of Hcy and Cys from spiked samples were 90.87–100.25%, and the relative standard deviations (RSD %) were 1.56–9.13%. The established method is simple, accurate, sensitive, and suitable for the separation and determination of Hcy and Cys in biological samples. Compared with the control group, the concentrations of Hcy and Cys in the diabetes group were different in the cortex. The difference suggests that changes in the levels of the two substances may be associated with complications of diabetes mellitus. Graphical Abstract: